2022
DOI: 10.3389/fpsyg.2022.778966
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Individual Differences in Executive Functions Predict Multitasking Performance – Implications for the Central Attentional Bottleneck

Abstract: Human multitasking suffers from a central attentional bottleneck preventing parallel performance of central mental operations, leading to profound deferments in task performance. While previous research assumed that the deferment is caused by a mere waiting time (refractory period), we show that the bottleneck requires executive functions (EF; active scheduling account) accounting for a profound part of the deferment. Three participant groups with EF impairments (dyslexics, highly neurotics, deprived smokers) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 92 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…Specifically, individuals with high WM capacity are generally better able to maintain cognitive control and remain task-focused (Engle, 2002;Engle & Kane, 2004). Therefore, it is suggested that participants with high WM capacity should exhibit fewer performance decrements in a primary task when concurrently performing a demanding secondary task (Szameitat et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, individuals with high WM capacity are generally better able to maintain cognitive control and remain task-focused (Engle, 2002;Engle & Kane, 2004). Therefore, it is suggested that participants with high WM capacity should exhibit fewer performance decrements in a primary task when concurrently performing a demanding secondary task (Szameitat et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In a second step, we investigated how task brain activity was modulated by individual differences in dual-task performance itself and other cognitive abilities. As mentioned earlier, dual-tasking implicates several cognitive processes (Worringer et al 2019) and shares variance with other subdomains of executive functioning (Himi et al 2019; Saylik et al 2022; Szameitat and Brunel Students 2022) to activate and maintain two task sets in parallel, control attentional processes and coordinate multiple actions. Furthermore, dual-task interference is affected by inter-individual differences and diverse contextual strategies to accomplish the tasks (Lehle and Hübner 2009; Hoffmann et al 2020).…”
Section: Introductionmentioning
confidence: 95%